Hit them in the wallet!: An analysis of the indian demonetization as a counter-insurgency policy - Edoardo Chiarotti; Nathalie Monnet (Graduate Institute of International and Development Studies, 2019)
In this paper, we study empirically how a policy targeting the cash-funding system of armed groups affects criminal activities, focusing on the 2016 Indian Banknote Demonetization as a natural experiment. We take advantage of a unique dataset on daily surrenders of the Maoist insurgents in India between 2006 and 2018. In order to measure the exposure of the conflict to the policy in different districts, we use three sources of access to funding for Maoists, namely mineral resources, public works' contractors and forest products. Our results suggest that there is a positive and significant impact of the demonetization on surrenders of Maoist extremists. We find a lower increase in surrenders where insurgents have higher abilities to raise new cash through mineral resources and public works, while we find a sharper increase in districts that rely on subsistence agriculture. This paper provides evidence that policies that curb illicit cash flows have the desired impact of deterring illegal and violent activities.
Keywords: C23; D74; Q34; E50; 330; Counterinsurgency; Conflict; Demonetization